SOSIALISASI PEMANFAATAN LIMBAH SAMPAH PLASTIK DI TAMBAK LEKOK KECAMATAN LEKOK KABUPATEN PASURUAN - Yusuf, Yusuf; Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
The aim of this outreach activity is to increase awareness of the role of utilizing plastic waste in the social and economic environment of the Tambak Lekok community, Lekok District, Pasuruan Regency, East Java Province. Implementation methods include initial interviews, counseling, education, and final interviews. The results of the activity showed an increase in public understanding and awareness after participating in the outreach activities. Participants better understand the importance of waste and plastic waste management in terms of sorting plastic waste, skills in making handicrafts and decorating the land/garden. This activity contributes to environmental cleanliness, environmental preservation, as well as added economic value to the residents of the Tambak Lekok community, Lekok District, Pasuruan Regency, East Java Province.